From Decentralization to Emission: Assessing the Climate Impact of DeFi Operations - Sendy, Sendy; Deniswara, Kevin (International Journal of Energy Economics and Policy, 2025)
Developments and changes in technology play a significant role in addressing climate change, one of which is decentralized finance, which is currently expanding, and it is still unclear whether it has a dynamic relationship with climate change. This study employs the TVP-VAR Connectedness model with the aim of analyzing the dynamic relationship between the decentralized finance operations and CO2 emissions, the impact of shocks from DeFi operations (Total Value Locked, Volume, Returns, Fees, and Revenues) dynamically increasing CO2 emissions, as well as to assess the role of DeFi returns in strengthening the transmissions of DeFi activity to CO2 emissions. The results show that DeFi operations have a dynamic relationship with CO2 emissions at a moderate level through shocks transmitted by DeFi operational indicators. It was also found that TVL acts more as a net receiver than a net transmitter, unlike Volume, Fees and Revenues. Returns do not significantly transmit shocks to CO2 emissions and are more exogenous in nature, while both TVL and Returns are predominantly influenced by internal idiosyncratic shocks. These findings emphasize the importance of integrating Green FinTech policies to ensure sustainable DeFi growth. The findings also provide important implications for regulators, industry practitioners and academics in their efforts to balance the advancement of DeFi with environmental sustainability.